IMPLEMENTASI HARGA POKOK PRODUKSI METODE FULL COSTING DALAM PENETAPAN HARGA JUAL DAN LABA DI KERUPUK JANGEK KHAS MALALO KOTA LUBUKLINGGAU - Eri Triharyati (Jurnal AkunStie (JAS), 2019)
This study aims to analyze the Implementation of Cost of Production Full Costing Method in Determination of Selling Prices and Profits in the Typical Jangek Malalo Crackers of Lubuklinggau City in 2015 until 2018. The results of the study on the calculation of Cost of Production in 2015 amounted to Rp.852.316,000, In 2016 amounting to Rp.865,932,000, in 2017 amounting to Rp.982,198,000 and Production Cost in 2018 known as Rp.1,183,192,000. Selling prices in 2015 and 2016 set by the cracker Jangek Malalo home industry amounted to Rp.120,000 / Kg and in 2017 and 2018 were Rp.130,000 / Kg, while the results of Researchers' calculations for 2015 Sale / Kg Prices were Rp.127,975 / Kg, in 2016 amounting to Rp.127,326 / Kg, in 2017 amounting to Rp.125,688 / Kg and in 2018 the Selling Price of Rp.127,699 / Kg. The researchers' calculation is assumed that the company targets or sets a profit of 10%, so the profit achieved by the cracker Jangek Malalo home industry is below 10% of the Production Cost for 2015 and 2016 while for 2017 and 2018 the company has achieved a profit above 10%. If the cracker Jangek Malalo Home industry wants to achieve a profit above 15% then the company must increase the selling price by multiplying the Cost of Production by 15%. For example, the selling price per kg of Rp.120,000 per month can be increased to Rp.133,792 / Kg and Rp.133,113 / Kg, whereas in the first month the selling price per kg of Rp.130,000 per kg can be increased to Rp.131.401/Kg and Rp. .13.50.50 / Kg.